Costruccion de escenarios futuros para el fortalecimiento de las mipymes del sector textil - Perlaza Paniagua, Raúl Esteban (2021)
The textile industry in Colombia is made up mostly of micro, small and medium enterprises (MSMEs), which according to the superintendency of industry and commerce are companies that employ from 2 to 400 workers and that invoice no more than 15,000 million pesos per year, It is a business model that in Colombia has been developed mostly through the SAS type of society since it allows a better adaptation to the business economic system,(Gonzalez Litman, 2016) With this article called "construction of future scenarios for the strengthening of MSMEs in the textile sector" it is sought to intervene in the sector by disclosing a methodology for the application and analysis of the variables that led to the design of the visionary scenario for the formulation of strategies favorable to a desired future, from the design of critical variables and their long-term behavior For the creation and analysis of this research, it was necessary to use MICMAC software (multiplication cross impact matrix applied to a classification), in which, taking into account the variables, the result of the information collected with actors in the sector through interviews, and the opinions of experts specialized in the issues in question, it was possible by consensus to evaluate and qualify the variables with which three future scenarios were created: the predictive scenario, the exploratory scenario and the visionary scenario. These future scenarios gave rise to the formulation of guidelines and strategies to achieve a long-term future, based on actions, plans and programs in the short and medium term.